2012
DOI: 10.1017/s1049023x12001173
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Application of Mobile Technology to Disaster Medicine

Abstract: Mobile health care technology (mHealth) has the potential to improve communication and clinical information management in disasters. This study reviews the literature on health care and computing published in the past five years to determine the types and efficacy of mobile applications available to disaster medicine, along with lessons learned. Five types of applications are identified: (1) disaster scene management; (2) remote monitoring of casualties; (3) medical image transmission (teleradiology); (4) deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Two notable recorded instances in which mobile technologies (specifically field hospital IT systems and teleradiology) were implemented in actual disasters were the US military in Pakistan in response to the 2005 earthquake and the Israeli Defence Forces in response to the 2010 earthquake in Haiti. Both cases showed that the electronic system in use helped with management of resources, identification and tracking of patients, and continuity of care and effective discharge [21]. …”
Section: Eemergency and Disaster Responsementioning
confidence: 99%
“…Two notable recorded instances in which mobile technologies (specifically field hospital IT systems and teleradiology) were implemented in actual disasters were the US military in Pakistan in response to the 2005 earthquake and the Israeli Defence Forces in response to the 2010 earthquake in Haiti. Both cases showed that the electronic system in use helped with management of resources, identification and tracking of patients, and continuity of care and effective discharge [21]. …”
Section: Eemergency and Disaster Responsementioning
confidence: 99%
“…In addition, technology has the potential to improve disaster patient tracking, patient data acquisition and monitoring, communications, incident management, inventory management, and EMS-ED coordination. 3,25,26 Information tools for mass casualty incidents must be carefully evaluated and ideally incorporated into routine, daily workflows or drills so they are familiar to ED staff when needed urgently.…”
Section: Resultsmentioning
confidence: 99%
“…This can be effective in reducing psychosocial barriers to certain health or medical treatments. Applications that promote shared transportation to town or city centers, or enable more timely connections to available vehicles, can also reduce physical access barriers (Case, Morrison & Vuylsteke, 2012). This can be particularly important for pregnant women in labor or ill children with rapidly deteriorating health conditions.…”
Section: Harnessing the Potentials Of Mhealthmentioning
confidence: 99%